Detection of Exhaled Volatile Organic Compounds Improved by Hollow Nanocages of Layered Double Hydroxide on Ag Nanowires. Issue 46 (30th September 2019) - Qiao, Xuezhi; Chen, Xiangyu; Huang, Chuanhui; Li, Ailin; Li, Xiao; Lu, Zhili; Wang, Tie
Abstract: To detect biomarkers from human exhalation, air flow dynamics on the nanoparticle surface were explored by a surface‐enhanced Raman scattering (SERS) sensor. A hollow Co‐Ni layered double hydroxide (LDH) nanocage on Ag nanowires (Ag@LDH) was prepared. Ag nanowires provided amplified Raman signals for trace determination; hollow LDH nanocages served as the gaseous confinement cavity to improve capture and adsorption of gaseous analytes. The Raman intensity and logarithmic analyte concentration exhibit an approximately linear relationship; the detection limit of SERS sensors for aldehyde is 1.9×10 −9 v/v (1.9 ppb). Various aldehydes in mixed mimetic gas are distinguished by Raman spectra statistical analysis assisted by multivariate methods, including principal component analysis and hierarchical cluster analysis. The information was recorded in a barcode, which can be used for the design and development of a desktop SERS sensor analysis system for large‐scale lung cancer detection. Abstract : You're the VOC : A high‐quality microarray well SERS sensor is used for aldehyde volatile organic compound detection. The integrated gas species information was recorded in a barcode that can be read rapidly, conveniently and accurately by a third instrument.